Funding public school infrastructure: an overview of selected impacts and reconceptualization of state aid, with insights from three representative Kansas school districts - Adams, Kellen James (Kansas State University, 2018)
The present study, Funding public school infrastructure: an overview of selected impacts and reconceptualization of state aid, with insights from three representative Kansas school districts sought to provide insights and new possibilities regarding public school infrastructure in the state of Kansas. The study was conducted in three separate, yet interconnected phases. Phase One provided for an in-depth literature review of past school finance formulae, litigation, and other important historical contexts at both a national level and more specifically within Kansas. Phase Two then sought to provide for an in-depth statistical analysis using common exploratory statistics of the three proposed funding alternatives to the bond and interest state aid formula. Finally, Phase Three provided for a practical application and lived experienced of the proposed alternatives through interviews with three selected school district representatives. Collectively, these three phases provided for a wealth of applicable and otherwise highly considerable solutions to the current funding mechanisms for capital infrastructure in the state of Kansas. The population for this study included all 286 school districts in the state of Kansas. The data used for the three proposed alternatives was provided by the Kansas State Department of Education and is from the 2015 audited fiscal year reports. The three selected school districts that were chosen for deeper discussion and analysis were USD 446-Independence, USD 490-El Dorado, and USD 491-Eudora. Results from the study revealed a wealth of insights that are both plausible and considerable for policymakers and legislators. Alternative one, which proposed applying general fund principles to the bond and interest fund would provide for the most assistance to school districts, but represented a straight cost increase to the state. Alternative two, which replaced property value measures (assessed valuation) with income-based measures (median household income) was cost neutral to the state, with both winners and losers. The final alternative provided for a complete policy shift away from mill levies tied only to districts that had incurred debt and moved towards a mandatory and uniform mill rate across all districts, while also creating a surplus pool from which districts could draw for capital infrastructure spending. The final alternative was again cost neutral to the state with a number of winners and losers, but provided for a means to an end that neither of the other two alternatives provided – an avenue for school districts to obtain capital infrastructure funding that would not require a majority vote by district patrons. The present study provided both an analysis of the current state of affairs, as well as a challenge to abandon current policy structures and begin to rethink how bricks and mortar within the state of Kansas are funded. The growing backlog of deferred maintenance, as well as the conclusion that the accident of residence will affect a child’s educational experience served as the necessary precursors and motivation for the recommendations and conclusions that were provided as a result of this study.
Keywords: Capital infrastructure; State aid